Steal the rain: Interception loses and rainfall partitioning by a broad‐leaf and a fine‐leaf woody encroaching species in a southern African semi‐arid savanna. Issue 3 (15th March 2023) - Skhosana, Felix V.; Thenga, Humbelani F.; Mateyisi, Mohau J.; von Maltitz, Graham; Midgley, Guy F.; Stevens, Nicola
Abstract: Woody plant encroachment (WPE) has been found to alter ecosystem functioning and services in savannas. In rain‐limited savannas, increasing woody cover can reduce streamflow and groundwater by altering evapotranspiration rates and rainfall partitioning, but the ecological relevance of this impact is not well known. This study quantified the altered partitioning of rainfall by two woody plant structural types (fine‐ and broad‐leaved trees) across a gradient of encroachment in a semi‐arid savanna in South Africa. Averaged across both plant functional types, loss of rainfall through canopy interception and subsequent evaporation roughly doubled (from 20.5% to 43.6% of total rainfall) with a roughly 13‐fold increase in woody cover (from 2.4 to 31.4 m 2 /ha tree basal cover). Spatial partitioning changes comprised fourfold increases in stemflow (from 0.8% to 3.9% of total rainfall) and a decline in throughfall proportion of about two‐fifths (from 80.2% to 47.3% of total rainfall). Changes in partitioning were dependent on plant functional type; rainfall interception by the fine‐leaved multi‐stemmed shrub Dichrostachys cinerea was almost double that of the broad‐leaved tree Terminalia sericea at the highest levels of woody encroachment (i.e., 49.7% vs. 29.1% of total rainfall intercepted at tree basal area of 31.4 m 2 /ha) . Partitioning was also dependent on rainfall characteristics, with the proportion of rainfall intercepted inversely related to rainfall event size and intensity. Therefore, increasing tree cover in African grassy ecosystems reduces the amount of canopy throughfall, especially beneath canopies of fine‐leaved species in smaller rainfall events. Rainfall interception traits may thus confer a selective advantage, especially for fine‐leaved woody plant species in semi‐arid savannas. Abstract : This study quantified the altered partitioning of rainfall by two woody plant structural types (fine‐ and broad‐leaved trees) across a gradient of encroachment in a semi‐arid savanna in South Africa. At the highest woody cover, rainfall loss through canopy interception by a fine‐leaved shrub Dichrostachys cinerea almost doubled that of a broad‐leaved tree Terminalia sericea . Rainfall partitioning was also dependent on rainfall characteristics, with the proportion of rainfall intercepted inversely related to rainfall event size and intensity.